Taurine ameliorates neuropathy via regulating NF-?B and Nrf2/HO-1 signaling cascades in diabetic rats (vol 71, pg 116, 2014) - Agca, Can Ali; Tuzcu, Mehmet; Hayirli, Armagan; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2015)
[Abstract Not Available]